2016 Kansas Performance Tests with Soybean Varieties - Lingenfelser, Jane; Schapaugh, William T.; Stephens, Cheyenne (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2018)
Soybean performance tests are conducted each year to provide information on the relative performance of new and established varieties and brands at several locations in Kansas. Seeds for tests are from private seed companies, certified growers, and agricultural experiment stations (Table 1). Seed quality, including factors such as purity and germination, can be important in determining the performance of a variety. Soybean seed used for private and public entries in the Kansas Crop Performance Tests is prepared professionally and usually meets or exceeds Kansas Crop Improvement Certification standards. Relative performance of a given variety comparable to that obtained in these tests is best assured under similar environmental conditions and cultural practices and with the use of certified or professionally prepared seed. All companies known to be developing and marketing soybean varieties or brands are invited to submit test seed; interested companies enter on a voluntary, fee-entry basis.
Keywords: Soybeans; Seeds; Yields; Environmental factors; Kansas